2018
DOI: 10.1177/1359104518757289
|View full text |Cite
|
Sign up to set email alerts
|

Conners 3–Self-Report Scale: An empirical support to the dimensionality of the content scales

Abstract: The Conners' Rating Scales are one of the most used instruments for attention deficit/hyperactivity disorder (ADHD). Nonetheless, in the latest edition, the Inattention scale was not statistically supported. This study examined the dimensionality of the Italian version of the Conners 3-Self-Report scale testing both a five-factor structure including Inattention and a four-factor model combining Inattention and Learning Problems. Moreover, the generalizability of the detected structure through measurement invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The advantages of the Conners scales have been supported by both studies confirming the excellent psychometric properties of the scales (e.g. Arias Martínez, Arias González, & Gómez Sánchez, 2013; Christiansen et al, 2016; Conners, Sitarenios, Parker, & Epstein, 1998; Izzo, Donati, & Primi, 2018a, 2019; Morales-Hidalgo, Hernández-Martínez, Vera, Voltas, & Canals, 2017) and clinical studies. In fact, research has demonstrated the effectiveness of the Conners scales in distinguishing people with ADHD from those with no clinical diagnoses; moreover, the Conners scales have been found to have predictive validity for the development of behavioral problems in adolescence (e.g.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The advantages of the Conners scales have been supported by both studies confirming the excellent psychometric properties of the scales (e.g. Arias Martínez, Arias González, & Gómez Sánchez, 2013; Christiansen et al, 2016; Conners, Sitarenios, Parker, & Epstein, 1998; Izzo, Donati, & Primi, 2018a, 2019; Morales-Hidalgo, Hernández-Martínez, Vera, Voltas, & Canals, 2017) and clinical studies. In fact, research has demonstrated the effectiveness of the Conners scales in distinguishing people with ADHD from those with no clinical diagnoses; moreover, the Conners scales have been found to have predictive validity for the development of behavioral problems in adolescence (e.g.…”
mentioning
confidence: 64%
“…The psychometric properties of the full-length forms of the Conners 3 scales have been previously tested and confirmed in cultural contexts different from the original one (Christiansen et al, 2016; Izzo et al, 2018a, 2019). Differently, the psychometric properties of the short forms of the Conners 3 have not been tested by any other study but the original one—in both the English version and the Spanish version, which was validated for the Spanish-speaking population of the United States (Conners, 2008).…”
mentioning
confidence: 95%
“…However, in a recent study examining the German version of the Conners 3 scales (Christiansen et al, 2016), CFAs were conducted on all Content scales, including the Inattention scale, with results revealing a good fit and supporting the Inattention scale with psychometric evidence. Moreover, empirical data from a recent Italian study (Izzo et al, 2018) confirmed this structure with the Inattention scale as a separate factor, though analyses were performed only for the Conners 3-SR scale. Thus, the first aim of the present work (Study 1) was to examine the dimensionality of the Conners 3-P and Conners 3-T scales to test whether the original structure could be confirmed and whether there is empirical support for the Inattention scale as a stand-alone factor.…”
Section: Introductionmentioning
confidence: 92%
“…Given that the Conners 3 Rating Scales are widely used in both clinical and research contexts, the present study aimed at assessing the psychometric properties of the Italian version of the Conners 3 scales in their parent and teacher versions to test whether they represented a reliable and valid instrument to assess ADHD in children and youth. In fact, as the psychometric properties of the Conners 3-SR scale were already investigated before (see Izzo, Donati, & Primi, 2018), and that hetero-assessments make it possible to gather information that people filling a self-evaluation may be unaware of, this research examined the psychometric properties of the Conners 3-P and the Conners 3-T scales in terms of the dimensionality of these scales, their reliability, and cross-informant agreement.…”
Section: Introductionmentioning
confidence: 99%
“…The Conners Rating Scales (Conners, 1989, 1997, 2008) that have a history of more than 30 years are used extensively in clinical and research settings for screening and diagnosis of attention-deficit hyperactivity disorder (ADHD) and comorbid disorders in children and adolescents (Izzo, Donati, & Primi, 2018). The rating scales are currently in its third edition, and are called Conners 3 (C 3; Conners, 2008).…”
mentioning
confidence: 99%